(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
This study investigates the effect of thinning the inflorescences of the ‘Khusayne beliy’ grape cultivar by removing certain parts before flowering on yield quantity and quality. Different thinning methods were applied, including removal of clusters from the upper, middle, and tip portions of the inflorescence in varying proportions. Results showed that thinning improved berry size, bunch uniformity, sugar content, and overall appearance, while total yield slightly decreased depending on the thinning method. Among the variants, thinning by alternately removing the middle part shoulders of the inflorescence produced the best quality grapes in terms of berry weight, diameter, and sugar content, making it a recommended practice for table grape production.